Relationship of Road Pavement Deformation Moduli, Determined by Different Methods - Giedrius Siaudinis (The Baltic Journal of Road and Bridge Engineering)
Deformations, caused by the axle loads of moving vehicles, are one of the main causes for pavement degradation. Measurement of elastic deflections is the best way to identify this effect. Currently, pavement deflections are most widely measured by the Falling Weight Deflectometer (FWD). Lithuanian standard LST 1360.5 "Soils for the motor roads" defines the measurement of deformations by static testing equipment at the top of each structural pavement layer. Based on the FWD-measured deflections at pavement surface, it is possible to calculate deformation moduli of structural pavement layers. In Lithuania deformation moduli are calculated by the ELMOD (Evaluation of Layer Moduli and Overlay Design) software. The results of experimental investigation of deformations of structural pavement layers by static and dynamic devices showed that the structural strength of road pavement, measured by the FWD, is close to the strength, measured by a static testing device. There is a linear relationship between E moduli, determined by static and dynamic methods. Investigation shows that the Falling Weight Deflectometer is suitable to determine the structural strength of investigated road pavements. However, more detailed investigations are necessary to identify the suitability of FWD to determine the structural strength of the other types of road pavement structures.